2007
DOI: 10.1016/j.euroecorev.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Microeconomic uncertainty and macroeconomic indeterminacy

Abstract: We are most grateful to Jorge Duran, R. Dos Santos Ferreira, L. Kaas and two anonymous referees for detailed and stimulating comments on these earlier versions. We also wish to thank (without implicating) R. Boucekkine, D. de la Croix, J.H.Drèze and participants at various seminars for thoughtful questions and comments. Financial support from the IAP IV and ARC programmes is gratefully acknowledged. AbstractThe paper proposes a stylized intertemporal macroeconomic model wherein the combination of decentralized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Most papers introducing imperfections in the product market assume monopolistic wholesalers, as Blanchard and Giavazzi (2003), Messina (2006) or the recent DSGE literature (see for instance Christiano et al (2005) or Smets and Wouters (2003)). Alternatively, in Fagnart et al (2007), wholesalers experience privately observed and uninsured idiosyncratic shocks, which generates a sub-optimal equilibrium. But none of these approaches allow for bilateral relationships and negotiations between wholesalers and retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Most papers introducing imperfections in the product market assume monopolistic wholesalers, as Blanchard and Giavazzi (2003), Messina (2006) or the recent DSGE literature (see for instance Christiano et al (2005) or Smets and Wouters (2003)). Alternatively, in Fagnart et al (2007), wholesalers experience privately observed and uninsured idiosyncratic shocks, which generates a sub-optimal equilibrium. But none of these approaches allow for bilateral relationships and negotiations between wholesalers and retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in Fagnart et al (2007), wholesalers experience privately observed and uninsured idiosyncratic shocks, which generates a sub-optimal equilibrium. But none of these approaches allow for bilateral relationships and negotiations between wholesalers and retailers.…”
Section: Ecb Working Paper Series No 1036mentioning
confidence: 99%